Tafsir Al-Qur’an Bi Al-Ma’thur: Satu Analisa Terhadap Tafsir Al-Qur’an Bi Al-Qur’an dan Tafsir Al-Qur’an Bi Al-Hadith - Hj. Mohd. Yusoff, Zulkifli (Jurnal Usuluddin, 1997)
This article tries to look into the concept of the Tafsir al-Qur’an bi al-Ma’thur. The discussion is made from it’s two perspective. The first analyses the Tafsir al-Qur’an bi al-Quran which is a part of Tafsir bi al-Ma’thur based on the classical clasification. The second is about the second sources of the Tafsir bi al- Ma’thur, i.e. Tafsir al-Qur’an bi al-Hadith.